Corporate fraud and bank loans: Evidence from China - Yunsen Chen; Song Zhu; Yutao Wang (China Journal of Accounting Research, 2011)
Receiving punishment from regulators for corporate fraud can affect financing contracts between a firm and its bank, as both the firm's credit risk and information risk increase after punishment. By focusing on Chinese firms' borrowing behavior after events of corporate fraud, we find that firms' bank loans after punishment are not only significantly lower, but are also less than those for non-fraudulent firms. In addition, loan interest rates after punishment are not only higher than before, but also higher than those for their non-fraudulent counterparts. In addition, we find that corporate fraud indirectly destabilizes the 'performance-bank loan' relationship. Our results suggest that corporate fraud negatively affects a firm's ability to source debt financing, which provides new evidence about the economic consequences of fraud.
Keywords: G32; G21; G38; 650; Corporate fraud; Bank loans; Credit risk; Information risk; China